(untitled) (Research, Society and Development, 2021)
Youth and Adult Education (EJA) is a teaching modality impregnated with dilemmas, but it can become potentially emancipatory and transformative, as advocated by Paulo Freire, with the inclusion of Critical Environmental Education in classes. In this context, this research aimed to understand the impact of interventions in Environmental Education in the teaching of Mathematics through Didactic Sequences, based on Freirian assumptions, with EJA students, in relation to their conceptions about their environmental reality. Thus, we developed a qualitative research, specifically, a case study, with the students of Mathematics – Elementary School II at EJA in the city of Paranavaí - PR. From the analysis of the data obtained with the implementation of the Didactic Sequence "Industrial Revolution, Urbanization Process and its Implications for the Environment", we found that the predominant conception of the Environment among the students was related to "Nature", that is, for them the environment is associated with the presence of forests, animals and plants. Another factor observed was the students’ lack of confidence in their ability to resolve activities, which was an obstacle to be overcome daily in the teaching and learning process. Given this context, we conclude that it is extremely relevant for EJA that more actions with this focus are carried out, because when problematizing socio-environmental aspects in the teaching of Mathematics in EJA, in order to value the knowledge and environmental reality of students, the teaching process and learning becomes more meaningful and potentially transformative.